1999
DOI: 10.1046/j.1365-2435.1999.00299.x
|View full text |Cite
|
Sign up to set email alerts
|

Using elasticity analysis of demographic models to link toxicant effects on individuals to the population level: an example

Abstract: Summary 1.A simple two-stage population model was applied to data from a previously published life-table response experiment (LTRE), which examined the toxicity of 4-n-nonylphenol to life-history traits of the polychaete Capitella sp. I. Population growth rates (λ) and the relative sensitivities (= elasticities) of λ to changes in each of the individual life-history traits were calculated. 2. In the present study, the life-history parameters measured in laboratory-reared individuals were manipulated to simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…In other words, density dependence will act to buffer the effects of toxicant exposure on population dynamics, consistent with a less-than-additive model. Hansen et al (1999) simulated potential influences of competition and predation on population-level response of the polychaete Capitella capitata (Type I) to 4-n-nonylphenol. By considering scenarios in which fecundity was reduced, time to maturity was extended, and/or juvenile survival was reduced by realistic amounts, the authors explored how the sensitivity of population growth rate to toxicant-caused changes in individual life-history traits was influenced.…”
Section: Results From Simulation Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, density dependence will act to buffer the effects of toxicant exposure on population dynamics, consistent with a less-than-additive model. Hansen et al (1999) simulated potential influences of competition and predation on population-level response of the polychaete Capitella capitata (Type I) to 4-n-nonylphenol. By considering scenarios in which fecundity was reduced, time to maturity was extended, and/or juvenile survival was reduced by realistic amounts, the authors explored how the sensitivity of population growth rate to toxicant-caused changes in individual life-history traits was influenced.…”
Section: Results From Simulation Studiesmentioning
confidence: 99%
“…Although the relationship between PGR and the individual life-history traits contributing to it is predictable, e.g., by the EulerLotka equation, the sensitivity of PGR to changes in the different traits is not obvious. It appears that the sensitivity of PGR to changes in the traits contributing to it depends on (1) the starting value of PGR, (2) the absolute values of the traits (i.e., the life-history type of the organism), and (3) the relative responsiveness of the different traits to toxicant exposure (Calow et al 1997, Hansen et al 1999Forbes et al 2001).…”
Section: Individual-vs Population-level Interactions: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The most common population-level measure of toxicity is its effect on the popula-tion growth rate (PGR), which can be expressed as the continuous growth rate r per unit time, or by the discrete multiplicative rate, λ, where λ = e r (Hansen et al, 1999;Stark and Danken, 1999;Forbes et al, 2000;Kuhn et al, 2000;Stark and Vargas, 2003;Stark, 2005). Forbes and Calow (1999) concluded that the PGR is a better response variable than individual-level endpoints, such as condition factor or fecundity, since r explicitly integrates individual-level responses to contaminants at the population level.…”
Section: Approaches To Quantifying Toxicity In Aquatic Organismsmentioning
confidence: 99%
“…Forbes and Calow (1999) concluded that the PGR is a better response variable than individual-level endpoints, such as condition factor or fecundity, since r explicitly integrates individual-level responses to contaminants at the population level. Hansen et al (1999) performed sensitivity analyses of the PGR with respect to changes in life-history traits of the polycheate Capitella. Similarly, Forbes et al (2000) analyzed the elasticity of the PGR with respect to life cycle variables in a semelparous benthic macroinvertebrate, an iteroparous fish, a daphnid, and an algal species.…”
Section: Approaches To Quantifying Toxicity In Aquatic Organismsmentioning
confidence: 99%